2017
DOI: 10.1007/s10865-017-9905-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated inflammation in association with alcohol abuse among Blacks but not Whites: results from the MIDUS biomarker study

Abstract: Some studies document racial disparities in self-reported health associated with alcohol use and abuse. However, few studies examined biomarkers that underlie the onset of alcohol-related chronic diseases. We investigated whether the association between alcohol abuse and five biomarkers of inflammation (CRP, IL-6, fibrinogen, E-selectin, sICAM-1) vary between Black and White Americans aged 35 to 84 (n = 1173) from the Midlife in the United States Biomarker Study. Multivariable Ordinary Least Squares regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
(88 reference statements)
0
12
0
Order By: Relevance
“…All of the interaction findings in the present research were exploratory and would require replication and greater probing (ideally with larger samples) prior to making any conclusions. Taken together, however, particularly in light of racial disparities in inflammation that appear to exist even beyond effects of socioeconomic status (Herd, Karraker, & Friedman, 2012; Ransome et al, 2018), these exploratory moderation analyses support the importance of having diverse samples and of examining sociodemographic differences that may relate to the connection between psychological phenomena and health.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…All of the interaction findings in the present research were exploratory and would require replication and greater probing (ideally with larger samples) prior to making any conclusions. Taken together, however, particularly in light of racial disparities in inflammation that appear to exist even beyond effects of socioeconomic status (Herd, Karraker, & Friedman, 2012; Ransome et al, 2018), these exploratory moderation analyses support the importance of having diverse samples and of examining sociodemographic differences that may relate to the connection between psychological phenomena and health.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the present sample was comprised of a majority of African-American participants and a sizable minority of Hispanic participants. Recent studies have revealed significantly higher CRP levels among African-Americans compared to White participants (Gruenewald, Cohen, Matthews, Tracy, & Seeman, 2009; Herd et al, 2012; Ranjitet al, 2007; Ransome et al, 2018). Thus, the present sample may be more representative of at least certain populations than many other studies, which frequently exclude individuals on the basis of health conditions and which are often predominately White.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] When this is compared with other studies, such as blacks and whites in America in terms of BMI, hs-CRP and ICAM-1, there is an upward trend in BMI followed by increases in hs-CRP and ICAM-1. [59] In terms of hs-CRP levels in the current study population, compared with other studies. [24,59,60] All subjects, regardless of cardiovascular risk, hs levels -CRP less than 1 mg/L, however, further investigation is required for polymorphism.…”
Section: Inflammatory Biomarkersmentioning
confidence: 88%
“…[59] In terms of hs-CRP levels in the current study population, compared with other studies. [24,59,60] All subjects, regardless of cardiovascular risk, hs levels -CRP less than 1 mg/L, however, further investigation is required for polymorphism. The implication of the classification of cardiovascular risk based on hs-CRP levels needs to be reviewed for the Javanese populations.…”
Section: Inflammatory Biomarkersmentioning
confidence: 88%